Pengembangan Desain Konseptual Pembelajaran Apresiasi Sastra melalui Integrasi Strategi BKAS dan Pembelajaran Berdiferensiasi - Padmarani, Kejora (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Literary appreciation instruction plays a crucial role in developing students’ critical and creative thinking skills, as well as their aesthetic sensitivity. However, school practices remain monotonous and do not yet accommodate the diversity of students’ characteristics. The Guidance Strategy for Literary Criticism and Appreciation (BKAS) is effective in developing appreciation skills, but it does not fully address differences in learning needs. Differentiated instruction provides flexibility in the learning process, but it has not been widely applied specifically in the context of literary appreciation. This study aims to develop a conceptual design for literary appreciation instruction through the integration of the BKAS strategy and differentiated instruction. The study employs a qualitative approach using a literature review based on national journals and relevant references from the past five years, analyzed using content analysis techniques. The results of the study indicate that the integration of BKAS strategies and differentiated instruction can produce a flexible, adaptive, and student-centered instructional design. This design is capable of increasing student engagement while developing critical and creative thinking skills. However, it remains conceptual and has not yet been empirically tested, thus requiring further research.